Relaxation Response in Stressed Volunteers: Psychometric Tests and Neurotrophin Changes in Biological Fluids - Zappella, Miriam; Biamonte, Filippo; Balzamino, Bijorn Omar; Manieri, Rocco; Cortes, Magdalena; Santucci, Daniela; Di Stasio, Enrico; Rizzuto, Maurizio; Micera, Alessandra (Frontiers in Psychiatry, 2021)
Background: To evaluate the beneficial effects of the Relaxation Response (RR) training in adult stressed subjects by evaluating the Psychometric response recorded at relaxation session. Cortisol as well as NGF and BDNF mediators were quantified in both saliva and tears, and their levels were related to each other and to the psychometric response. Methods: Stressed subjects (n= 23; 10M/13F; age range 21-55 years old) were voluntarily enrolled in the study. RR training sessions were carried out for two months, one day per week, at the same time (3pm to 5pm). Two different psychological questionnaires, the Perceived Stress Scale-10 (PSS-10) and the Beck Depression Inventory - Short Form (BDI-SF) and the ocular surface symptomatic (OSDI) tests were administered before each session. Saliva and tears were sampled for cortisol (EIA), NGF (ELISA) and BDNF (ELISA) quantifications. Questionnaire’s data were analysed and compared to biochemical ones Results: All subjects reported beneficial effects from training. RR significantly reduced the psychological stress indexes (p=0.039 for PSS-10 and p=0.001 for BDI-SF). Specifically, RR training lowered the perception of Perceived Helplessness (items 1,2,3,6,10; p<0.05) in PSS-10, increasing the Perceived Self-Efficacy (p<0.05). OSDI grading was in the normal range (0 – 25). Biochemically, a decrease in cortisol, a trend to a decrease in NGF and an increase in BDNF levels were observed in saliva samples after RR treatment. Furthermore, a trend to a decrease in NGF and an increase in BDNF were quantified in tear samples. A correlation between PSS-10 total score and saliva NGF variation (%) as well as between BDI-SF total score and BDNF tear levels were also observed. Conclusion: RR training appeared useful to lowering psychological, mental and physical stress, as supported by both psychological total and single scores. The finding on biochemical levels of BDNF in salive and tears are sustained by previous studies while those of NGF require further investigation. Overall, these data on a small population highlight the potential use of RR training and potential neurotrophic changes in biological fluids, in stressed volunteers.